Akkermansia muciniphila suppressing nonalcoholic steatohepatitis associated tumorigenesis through CXCR6+ natural killer T cells - Li, Tao; Lin, Xinlong; Shen, Binhai; Zhang, Wujian; Liu, Yangyang; Liu, Hongbin; Wang, Ye; Zheng, Lijun; Zhi, Fachao (Frontiers in Immunology, 2022)
Introduction Gut microbiota plays a crucial role in the development and progression of nonalcoholic steatohepatitis (NASH) and associated hepatocellular carcinoma (HCC). Akkermansia muciniphila was reported to inhibit inflammation-associated cancer in the intestine. The anti-NASH ability of A. muciniphila has recently been found. Thus, we were to investigate whether supplementation of A. muciniphila could prevent NASH-associated HCC. Methods In a model we called STAM, male C57BL/6J mice were subcutaneously injected with 200 µg streptozotocin at 4 days after birth, and fed with high-fat diet at 4 weeks of age to induce NASH-associated HCC. Faeces from mice and patients with NASH-related HCC were collected for 16S rRNA sequencing. STAM mice were orally administered either saline or A. muciniphila twice a day starting at 4 or 10 weeks of age. The effects of A. muciniphila on the immune responses were also evaluated. Results Patients and mice with NASH-related HCC showed significantly reduced gut A. muciniphila in comparison to healthy controls. Administration of breast milk-isolated A. muciniphila (AM06) but not feces-isolated A. muciniphila (AM02) could improve NASH severity. Interestingly, breast milk-isolated A. muciniphila treatment suppressed the progression of NASH to HCC, accompanied with an increased hepatic CXCR6+ natural killer T (NKT) cell and decreased macrophage infiltration. The antitumor ability of A. muciniphila was not evident in NKT cell-deficient mice (CD1d-/- and CXCR6-/-). In vitro, A. muciniphila promoted the killing of hepG2 cells by NKT cells. Discussion Our study will provide the rationale for the application of A. muciniphila to treat NASH and for the prevention of its progression to HCC.